Crystal structure of ω-Al4Cr - Changzeng Fan; Cong Liu (IUCrData, 2018)
The new polymorph of tetraaluminium chromium, Al4Cr, designated as the ω-phase, was obtained as the product from a high-pressure sintering (HPS) process of a stoichiometric Al4Cr mixture. The crystal structure is isotypic with Al4Mo and Al4W. The unit cell of ω-Al4Cr is much smaller than any of the other reported Al4Cr polymorphs, containing 30 rather than several hundred atoms.